A Novel Tetrandrine-Loaded Chitosan Microsphere: Characterization and in vivo Evaluation [Retraction] - Guo K; Cang J (Dove Medical Press, 2022)
Guo K, Cang J. Drug Des Devel Ther. 2016;10:1291–1298. The Editor and Publisher of Drug Design, Development and Therapy wish to retract the published article. Concerns were raised regarding the alleged duplication of images in Figures 1 and 5 with the same images from other unrelated articles. Specifically, Figure 1B appears to have been duplicated with the same image from Figure 1B from Li & Gong, 2016 (https://doi.org/10.2147/DDDT.S113670). Figure 5A appears to have been duplicated with the same image from Figure 4Aa in Li & Gong, 2016 (https://doi.org/10.2147/DDDT.S113670) and Figure 5A, Lung from Chen et al, 2015 (https://doi.org/10.2147/DDDT.S81722). Figure 5B appears to have been duplicated with the same image from Figure 5A, Lung in Zhou et al, 2017 (https://doi.org/10.2147/DDDT.S146925). The authors did not respond to our queries and no explanation for the alleged image duplication was provided. The Editor requested to retract the article and the authors were notified of this. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.